2005
DOI: 10.1161/circulationaha.105.549527
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Fatal Arrhythmias in High-Risk Subjects by Fish Oil n-3 Fatty Acid Intake

Abstract: Background— The long-chain n-3 fatty acids in fish have been demonstrated to have antiarrhythmic properties in experimental models and to prevent sudden cardiac death in a randomized trial of post–myocardial infarction patients. Therefore, we hypothesized that these n-3 fatty acids might prevent potentially fatal ventricular arrhythmias in high-risk patients. Methods and Results— Four hundred two patients with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
227
0
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(244 citation statements)
references
References 27 publications
2
227
0
15
Order By: Relevance
“…Surprisingly, in the study by Raitt et al 23 recurrent episodes of ventricular tachycardia or fibrillation occurred more frequently in patients on n-3 PUFA, and the time to event was reduced. In contrast to these findings, Leaf et al 20 observed a trend towards an increase in time to recurrent ventricular tachycardia or fibrillation or death in the n-3 PUFA group in the Fatty Acid Arrhythmia Trial (FAAT) in which 402 patients with an ICD were randomized to either 2.6 g/day n-3 PUFA or olive oil for 1 year. Moreover, Brouwer and coworkers 24 found no strong evidence of a protective effect of omega-3 PUFA given at a daily dose of 0.9 g for 1 year as compared to that of sunflower oil, against ventricular arrhythmias in 546 patients with ICD, although a trend towards decreased ventricular arrhythmias or death was noted in the subgroup of patients with a prior myocardial infarction.…”
Section: Studies On Anti-arrhythmic Effectsmentioning
confidence: 92%
See 2 more Smart Citations
“…Surprisingly, in the study by Raitt et al 23 recurrent episodes of ventricular tachycardia or fibrillation occurred more frequently in patients on n-3 PUFA, and the time to event was reduced. In contrast to these findings, Leaf et al 20 observed a trend towards an increase in time to recurrent ventricular tachycardia or fibrillation or death in the n-3 PUFA group in the Fatty Acid Arrhythmia Trial (FAAT) in which 402 patients with an ICD were randomized to either 2.6 g/day n-3 PUFA or olive oil for 1 year. Moreover, Brouwer and coworkers 24 found no strong evidence of a protective effect of omega-3 PUFA given at a daily dose of 0.9 g for 1 year as compared to that of sunflower oil, against ventricular arrhythmias in 546 patients with ICD, although a trend towards decreased ventricular arrhythmias or death was noted in the subgroup of patients with a prior myocardial infarction.…”
Section: Studies On Anti-arrhythmic Effectsmentioning
confidence: 92%
“…Experimental work in animal models have shown that n-3 PUFA alter the electrophysiological properties of the heart, 20 and it has been suggested that stabilization of cell membranes might explain the anti-arrhythmic and anti-fibrillatory effects of n-3 PUFA. 21 The early effect of n-3 PUFA on total mortality and sudden death, as demonstrated by the time-course analysis of the results of the GISSI-Prevenzione study, supported a hypothesis of an anti-arrhythmic potential of n-3 PUFA.…”
Section: Studies On Anti-arrhythmic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological effects of n-3 FA on atherosclerosis include preventing arrhythmias [8,12,[19][20][21][22][23][24], decreasing platelet aggregation [27][28][29], lowering plasma triglycerides [30][31][32][33][34][35], increasing HDL cholesterol and LDL particle size [36][37][38][39][40], decreasing blood pressure [42][43][44][45], reversing cholesterol accumulation from atheromatous plaques [46,47] and decreasing inflammation [48][49][50].…”
Section: Biological Effects Of N-3 Fa Related To Cvdmentioning
confidence: 99%
“…In the GISSI trial, Macchia et al [19] found that the effect of n-3 FA on sudden death reduction was greater in patients with left ventricular systolic dysfunction, suggesting that one primary effect of n-3 FA therapy in patients with prior myocardial infarction is antiarrhythmogenic. Subsequent studies have suggested that the major impact of n-3 FA on arrhythmias is in patients with prior MI [12,20,21]. Chrysohoou et al [22] in a sample of Greek adults found that patients who consumed 300 g fish/week or more had a 29.2% lower likelihood of having QTc intervals >0.45 s (P=0.03), therefore n-3 FA could provide antiarrhythmic protection at a population level.…”
Section: Biological Effects Of N-3 Fa Related To Cvdmentioning
confidence: 99%